Virtual reality for tinnitus management: a randomized controlled trial. (3rd October 2022) - Deshpande, Aniruddha K.; Bhatt, Ishan; Rojanaworarit, Chanapong
Abstract: Objective: Sound therapy (ST) and stress reduction regimens have been successfully used to manage tinnitus. Virtual reality (VR) has been used to manage chronic conditions like intractable pain. The aim of the present study was to investigate whether the use of VR in conjunction with ST revealed additional improvements in tinnitus attributes as compared to ST alone. Design: This study was a randomised controlled trial (RCT) with a cross-over design. All participants received two interventions – ST alone (control) and ST with VR stimuli (experimental). ST consisted of fractal tones while VR stimuli comprised of nature videos presented via VR goggles. A multilevel mixed-effects linear regression model was used to estimate the intervention effect. Study sample: Twenty adults with subjective, continuous, chronic tinnitus participated in the study. Results: After adjusting for period and baseline tinnitus loudness, significant improvements were observed in tinnitus loudness and Tinnitus Functional Index scores. Although not statistically significant, mean minimum masking levels were lower after the experimental intervention. Conclusions: Study participants benefitted from the use of VR in conjunction with ST in a laboratory setting. Additional effectiveness trials and blinded RCTs will be needed before validating the use of VR for tinnitus management in clinical settings.